The Effect Of Composting With The Addition Of Sheep Manure On Decrease In Total Petroleum Hydrocarbon (Tph) Levels Of Top Soil Polluted By Waste Oil - Husnawati Yahya; Syafrina Sari Lubis; Maulida Maulida (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The increasing use of oil, the more used oil produced, so that the impact of pollution caused to the soil is also greater. Therefore, efforts are needed to process waste oil with a biological approach method known as bioremediation. Because bioremediation is one of the technologies or environmental management that is economical and effective by utilizing microbial activities such as bacteria. This study aims to see the effect of adding sheep manure on reducing TPH levels of top soil polluted with oil waste, the research conducted was the use of the composting method with the addition of sheep manure in the biodegradation process of soil polluted with oil waste. Sheep manure treatment consists of 3 levels of 0%, 30% and 50% addition of sheep manure with 4 kotrol repetitions (K1) and 4 repeat times on treatment (P1) and (P2). In this study, measurements of pH, temperature, humidity, TPH value and total bacterial colonies were carried out. The results of the sheep manure enhancer study with a concentration of 50% were able to reduce the mass of % TPH which was originally 10.8% to 1.2% after composting for 30 days with the effectiveness of TPH degradation of 88.8% on day 30. Total bacterial colonies obtained were 1.3x10 6 days 0, 5.6x10 6 on day 30 on control (K), on the 1st treatment (P1) on day 0 the number of colonies was 0.8x10 6, day 30 2.7x10 6 colonies, treatment 2 (P2) day 0 4.7x10 6 colonies on day 30 1.7x10 6 . The results showed that the time of composting and the addition of sheep manure concentration had an effect on decreasing the value of TPH.